2011
DOI: 10.1021/ma201595j
|View full text |Cite
|
Sign up to set email alerts
|

Sorbitol–POSS Interactions on Development of Isotactic Polypropylene Composites

Abstract: This study investigates the nature of interactions between the molecules of polyhedral oligomeric silsesquioxane (POSS) containing silanol functionalities (silanol–POSS) and di(benzylidene)sorbitol (DBS) encountered in the development of nanocomposite fibers from the compounds of POSS, DBS, and isotactic polypropylene (iPP). The interactions were investigated using Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), wide-angle X-ray diffraction (WAXD), nuclear magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 56 publications
4
63
0
Order By: Relevance
“…Similar type of dispersions were observed by Ayandele et al 11 and Roy et al 48 This increased the compatibility between the two components, leading to a nanosized dispersion of some POSS molecules. The TEM images showed slight increase in the aggregation pattern on increasing the POSS content from 5% to 20%.…”
Section: 31transmission Electron Microscopysupporting
confidence: 79%
“…Similar type of dispersions were observed by Ayandele et al 11 and Roy et al 48 This increased the compatibility between the two components, leading to a nanosized dispersion of some POSS molecules. The TEM images showed slight increase in the aggregation pattern on increasing the POSS content from 5% to 20%.…”
Section: 31transmission Electron Microscopysupporting
confidence: 79%
“…Great progress in the characterization of POSS species has been made with the use of mass spectrometry (MS), which allows the degree of intramolecular condensation to be readily determined from their MS spectra. [6] The production of intact ionized POSS molecules in the gas phase is usually achieved using matrix-assisted laser desorption/ionization (MALDI) [6][7][8][9][10][11][12][13][14][15][16][17][18] or electrospray ionization (ESI), [9,10,14,15,[19][20][21][22] although the use of alternative soft techniques such as fast atom bombardment (FAB) [23,24] or atmospheric pressure chemical ionization (APCI) [19,25] has also been reported. Despite the increasing number of studies involving mass spectrometry as an efficient tool to characterize these compounds, the activation of ionized POSSs to characterize their fragmentation pathways has rarely been documented.…”
mentioning
confidence: 99%
“…An alternative approach consists of combining commercially used nucleating agents with organic–inorganic materials . Roy et al . reported that the molecules of silanol silsesquioxanes and a sorbitol derivative, namely di(benzylidene)sorbitol, are capable of forming several complex molecular adducts, due to noncovalent interactions, i.e., hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%